Learn more about

Refine search

Results (displaying matches 1-50 of 51) Next

Label Class Equation Sato-Tate \(\overline{\Q}\)-simple \(\GL_2\) Rank*
169.a.169.1 169.a \(y^2 + (x^3 + x + 1)y = x^5 + x^4\) $E_6$ 0
2704.a.43264.1 2704.a \(y^2 = x^5 - 5x^3 - 5x^2 - x\) $E_6$ 0
3721.a.3721.1 3721.a \(y^2 + (x^3 + x + 1)y = -x^4 + x^3 + 3x^2 + x\) $E_6$ 2
3969.b.35721.1 3969.b \(y^2 + (x^3 + x + 1)y = -2x^5 + 3x^4 - 3x^2\) $E_6$ 2
3969.c.35721.1 3969.c \(y^2 + (x^2 + x)y = x^5 - 5x^4 + 4x^3 - x\) $E_6$ 0
8281.b.405769.1 8281.b \(y^2 + (x^3 + x + 1)y = -3x^5 + 9x^4 - 7x^3 - 2x^2 + x\) $E_6$ 2
8281.c.405769.1 8281.c \(y^2 + (x^2 + x)y = x^5 + 8x^4 + 11x^3 + 3x^2 - x\) $E_6$ 0
8649.b.700569.1 8649.b \(y^2 + (x^2 + x)y = 9x^5 + 2x^4 - 21x^3 - 22x^2 - 8x - 1\) $E_6$ 0
8649.c.700569.1 8649.c \(y^2 + (x^2 + x)y = x^5 + 9x^4 + 13x^3 + 4x^2 - x\) $E_6$ 0
11881.a.11881.1 11881.a \(y^2 + (x^2 + x)y = x^5 - 3x^4 + 2x^2 - x\) $E_6$ 0
12321.a.36963.1 12321.a \(y^2 + (x^3 + x + 1)y = x^5 + 3x^4 + 4x^3 + 2x^2\) $E_6$ 2
12544.a.12544.1 12544.a \(y^2 = x^5 + 2x^4 - x^3 - 3x^2 - x\) $E_6$ 0
12544.c.12544.1 12544.c \(y^2 = x^5 - 2x^4 - x^3 + 3x^2 - x\) $E_6$ 0
13689.a.13689.1 13689.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 4x^3 - 2x^2\) $E_6$ 2
13689.b.13689.1 13689.b \(y^2 + (x^2 + x)y = x^5 + 3x^4 + x^3 - 2x^2 - x\) $E_6$ 0
17689.a.17689.1 17689.a \(y^2 + (x^2 + x)y = x^5 - 4x^4 + 2x^3 + x^2 - x\) $E_6$ 0
17689.b.17689.1 17689.b \(y^2 + (x^3 + x + 1)y = -3x^4 - 3x^3 + x^2 + x\) $E_6$ 2
20736.f.186624.1 20736.f \(y^2 = x^5 - 2x^4 - 9x^3 - 7x^2 - x\) $E_6$ 0
20736.g.186624.1 20736.g \(y^2 = x^5 + 2x^4 - 9x^3 + 7x^2 - x\) $E_6$ 0
21316.a.42632.1 21316.a \(y^2 + (x^3 + x + 1)y = 3x^3 + 4x^2 + x\) $E_6$ 2
21904.e.350464.1 21904.e \(y^2 = x^5 + 3x^4 - 11x^3 + 8x^2 - x\) $E_6$ 0
24649.a.24649.1 24649.a \(y^2 + (x^2 + x)y = x^5 + 4x^4 + 3x^3 - x^2 - x\) $E_6$ 0
32761.a.32761.1 32761.a \(y^2 + (x^3 + x + 1)y = x^5 + 10x^2 + 19x + 10\) $E_6$ 2
37636.a.602176.1 37636.a \(y^2 + (x^3 + x + 1)y = x^5 + 4x^4 + 6x^3 + 3x^2\) $E_6$ 2
43264.c.43264.1 43264.c \(y^2 = x^5 - 5x^3 + 5x^2 - x\) $E_6$ 0
48841.b.830297.1 48841.b \(y^2 + (x^3 + x + 1)y = -x^6 + 2x^5 - 5x^4 + 6x^3 - 6x^2 + 2x - 1\) $E_6$ 0
52441.a.52441.1 52441.a \(y^2 + (x^2 + x)y = x^5 + 5x^4 + 5x^3 - x\) $E_6$ 0
76729.a.76729.1 76729.a \(y^2 + (x^2 + x)y = x^5 - 6x^4 + 6x^3 - x^2 - x\) $E_6$ 0
92416.a.92416.1 92416.a \(y^2 = x^5 - x^4 - 7x^3 - 6x^2 - x\) $E_6$ 0
92416.b.92416.1 92416.b \(y^2 = x^5 + x^4 - 7x^3 + 6x^2 - x\) $E_6$ 0
110889.a.110889.1 110889.a \(y^2 + (x^3 + x + 1)y = x^5 - 3x^4 - 3x^3 + 6x^2 - 3x\) $E_6$ 2
110889.b.110889.1 110889.b \(y^2 + (x^2 + x)y = x^5 + 6x^4 + 7x^3 + x^2 - x\) $E_6$ 0
123201.c.369603.1 123201.c \(y^2 + (x^3 + x + 1)y = x^4 + 5x^3 + 5x^2 + x\) $E_6$ 2
157609.a.157609.1 157609.a \(y^2 + (x^2 + x)y = x^5 - 7x^4 + 8x^3 - 2x^2 - x\) $E_6$ 0
177241.a.177241.1 177241.a \(y^2 + (x^3 + x + 1)y = x^5 - x^4 - 7x^3 + 8x^2 - 3x\) $E_6$ 2
188356.a.376712.1 188356.a \(y^2 + (x^3 + x + 1)y = x^5 - 2x^4 - 6x^3 - 3x^2\) $E_6$ 2
188356.b.376712.1 188356.b \(y^2 + (x^3 + x + 1)y = -4x^4 - 5x^3 + x\) $E_6$ 2
219961.a.219961.1 219961.a \(y^2 + (x^2 + x)y = x^5 + 7x^4 + 9x^3 + 2x^2 - x\) $E_6$ 0
219961.b.219961.1 219961.b \(y^2 + (x^3 + x + 1)y = -x^6 - 2x^5 + x^4 + 5x^3 - 3x - 1\) $E_6$ 0
232324.a.464648.1 232324.a \(y^2 + (x^3 + x + 1)y = -2x^5 + 2x^4 + 2x^3 - 4x^2\) $E_6$ 2
301401.a.301401.1 301401.a \(y^2 + (x^3 + x + 1)y = -x^6 - x^5 + 3x^4 + 4x^3 - 3x^2 - 4x - 1\) $E_6$ 0
301401.b.301401.1 301401.b \(y^2 + (x^2 + x)y = x^5 - 8x^4 + 10x^3 - 3x^2 - x\) $E_6$ 0
350464.a.350464.1 350464.a \(y^2 = x^5 - 3x^4 - 11x^3 - 8x^2 - x\) $E_6$ 0
391876.b.783752.1 391876.b \(y^2 + (x^3 + x + 1)y = -x^6 - 2x^5 + 3x^3 - x^2 - 3x - 1\) $E_6$ 0
405769.b.405769.1 405769.b \(y^2 + (x^3 + x + 1)y = -x^6 + 4x^5 - 5x^4 - 4x^3 + 4x^2 - 1\) $E_6$ 0
454276.a.908552.1 454276.a \(y^2 + (x^3 + x + 1)y = -x^5 - 4x^4 + 5x^2 + 2x\) $E_6$ 2
537289.a.537289.1 537289.a \(y^2 + (x^2 + x)y = x^5 - 9x^4 + 12x^3 - 4x^2 - x\) $E_6$ 0
537289.c.537289.1 537289.c \(y^2 + (x^2 + x)y = x^6 - 2x^5 - 3x^4 + 5x^3 + 2x^2 - 4x + 1\) $E_6$ 2
727609.a.727609.1 727609.a \(y^2 + (x^3 + x + 1)y = -3x^5 + 11x^4 - 11x^3 + x\) $E_6$ 2
900601.a.900601.1 900601.a \(y^2 + (x^2 + x)y = x^5 - 10x^4 + 14x^3 - 5x^2 - x\) $E_6$ 0
Next

Download all search results for